Violent Extremism Online: New Perspectives on Terrorism and the Internet - Stuart Macdonald (Routledge, 2016)
This book explores the interface between terrorism and the internet and presents contemporary approaches to understanding violent extremism online. It focuses on four issues in particular: terrorist propaganda on the internet; radicalisation and the internet; counter campaigns and approaches to disrupting internet radicalisation; and approaches to researching and understanding the role of the internet in radicalisation. The book brings together expertise from a wide range of disciplines and geographical regions including Europe, the US, Canada and Australia. These contributions explore the various roles played by the Internet in radicalisation; the reasons why terroristic propaganda may or may not influence others to engage in violence; the role of political conflict in online radicalisation; and the future of research into terrorism and the internet.